2022
DOI: 10.3390/s22134972
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the Best Set of Features for sEMG-Based Hand Gesture Recognition Applying a CNN Architecture

Abstract: The classification of surface myoelectric signals (sEMG) remains a great challenge when focused on its implementation in an electromechanical hand prosthesis, due to its nonlinear and stochastic nature, as well as the great difference between models applied offline and online. In this work, the selection of the set of the features that allowed us to obtain the best results for the classification of this type of signals is presented. In order to compare the results obtained, the Nina PRO DB2 and DB3 databases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Other studies focused on feature extraction, J.A. Sandoval-Espino et al [46] extracted four features in the time domain of the EMG signal for input into the CNN. Other studies have employed pattern recognition methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies focused on feature extraction, J.A. Sandoval-Espino et al [46] extracted four features in the time domain of the EMG signal for input into the CNN. Other studies have employed pattern recognition methods.…”
Section: Discussionmentioning
confidence: 99%
“…J.A. Sandoval-Espino et al [46] conducted an experiment using CNNs to analyze four sets of the time-domain features of EMG signals.…”
Section: Comparative Analysis With Other Methodsmentioning
confidence: 99%
“…Consequently, they can be employed in real-time applications. Furthermore, they have been demonstrated to achieve high gesture recognition accuracy (exceeding 90%) when combined with machine learning classifiers [ 56 , 57 ]. Nevertheless, time-frequency-domain features, such as Short-Time Fourier Transform (STFT) coefficients, Spectral Moment (SM), and Stockwell Transform coefficients, have the potential to capture non-stationarities in sEMG signals.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, time-frequency-domain features, such as Short-Time Fourier Transform (STFT) coefficients, Spectral Moment (SM), and Stockwell Transform coefficients, have the potential to capture non-stationarities in sEMG signals. However, studies have not conclusively demonstrated superior performance over time-domain features, which would justify the added computational complexity for many applications [ 56 , 58 , 59 ]. After extracting 37 features from each of the eight sEMG channels, we tested the performance of the kNN classification algorithm using the database containing 296 features (37 × 8 = 296).…”
Section: Methodsmentioning
confidence: 99%
“…For real-time wearable sEMG devices, the total response time of myoelectric control should be limited to 300 ms [ 25 , 26 , 27 ]. A wide window function bandwidth results in a low time-domain resolution, and a narrow window function bandwidth results in a low frequency-domain resolution [ 28 ].…”
Section: Experimental Methodsmentioning
confidence: 99%